Plyometric method as a tool for muscle strength optimization in trained youth. Systematic Review (Original) (Revista científica Olimpia, 2021)
Nowadays there are several methods for the development and optimization of muscular strength, the present study emphasizes the Plyometric method (PL) which is characterized by its direct relationship with muscular and explosive strength in its fast cycle of elongation (eccentric phase) and muscle shortening (concentric phase) CEA. As part of a moderate and intense physical exercise and to have a healthy life it is necessary to know and practice exercises that involve cardiovascular development, likewise, it is recommended several moderate or intense exercises with the own body weight or with the use of extra weights to strengthen the muscles of the body, therefore, the research conducted is from the search for information on the PL method in young people. Objective: To analyze the plyometric method by means of a systematic review, for the strengthening of muscular strength in a trained youth population. Methodology: The main search engine used was Google Scholar and the following databases: Scielo, Dialnet, Science Direct and Redalyc, the search for information was carried out using the keywords "Plyometric method" or "plyometric training" and "explosive strength" or "muscular strength" and "Youth". Results: the articles analyzed are from the last 5 years, 13 results were obtained, with representation of the plyometric method, muscular strength, explosive, training and young population. Conclusions: The intervention of a PL method is an effective form of training for the strengthening of muscular strength in trained young people regardless of the discipline they practice.
Keywords: plyometric method (pl), training, muscular strength, explosive strength